PERAN CROSS SELLING TERHADAP PENINGKATAN TRANSAKSI POSPAY DI KANTOR POS SOREANG KABUPATEN BANDUNG (STKIP PGRI Jombang, 2022)
This research aims to determine the role of cross-selling on the increase in Pospay transactions at the Soreang Post Office, Bandung District. This research is done due to the decreasing number of Pospay transactions at the Soreang Post Office, Bandung District. It used a qualitative method with descriptive analysis techniques. This research was conducted from November 2021 to December 2021 by applying the Cross-Selling technique. It analyzed the Pospay transaction data for the period of January to December 2021 for one year. Cross-selling is a technique of selling goods/services that are related to one another (Sunandar & Lubis, 2018). The results of this study show that Cross-Selling can increase Pospay transactions, where Pospay transactions continue to increase every month. In November, Pospay transactions increased to 285 transactions, or 15.5% higher than in October. It also increased in December to 214 transactions or 10.1%. Thus the use of Pospay through Cross-Selling techniques can be maximized in the future by adjusting to the times.